2013
DOI: 10.2118/135563-pa
|View full text |Cite
|
Sign up to set email alerts
|

CO2 Injection in Vertical and Horizontal Cores: Measurements and Numerical Simulation

Abstract: Summary In certain high-pressure and low-temperature reservoirs, the density of CO2 may be substantially higher than the oil density. Upon mixing of CO2 and oil, a gas phase with a high content of methane (C1) may also appear. When the C1 content is high, this gas phase may have a lower density than the oil. In relation to this phenomenon, we have conducted three comprehensive experiments studying CO2 injection from the top and bottom of a vertical core and injection in a horizontal core. The in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(36 citation statements)
references
References 2 publications
2
34
0
Order By: Relevance
“…The gravity number in horizontal flow is higher than that in vertical flow. Moortgat et al [24] observed a similar gravitational effect during their study in which oil recovery was compared between core flooding in horizontal, vertical up, and vertical down CO 2 flooding. In their study, CO 2 density was higher than the oil density used; hence, gravitational frontal instability was observed during vertical CO 2 injection from top to bottom.…”
Section: Residual Saturationmentioning
confidence: 64%
“…The gravity number in horizontal flow is higher than that in vertical flow. Moortgat et al [24] observed a similar gravitational effect during their study in which oil recovery was compared between core flooding in horizontal, vertical up, and vertical down CO 2 flooding. In their study, CO 2 density was higher than the oil density used; hence, gravitational frontal instability was observed during vertical CO 2 injection from top to bottom.…”
Section: Residual Saturationmentioning
confidence: 64%
“…These changes are mainly attributed to physics and chemical interaction between the two fluids and also to the fluid injection rate and pressure [1]. The many advantages of CO 2 injection over those of water and nitrogen injection are summarized in [2]. CO 2 flooding is among the most promising enhanced oil recovery (EOR) methods in heavy oil reservoirs and has been successfully used in a number of worldwide basins where other EOR techniques are not applicable [3].…”
Section: Introductionmentioning
confidence: 99%
“…The swelling depends on the amount of methane in the oil. Because the CO 2 does not displace all of the methane when it contacts a reservoir fluid, the more methane there is in the oil, the less is the swelling of the oil [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nasrabadi et al [6] conducted the simulation study to investigate the effect of density in the 2D vertical reservoir and shown significant effect of gravity and heterogeneity. Although a number of researchers [1][2][3][4][5][6][7][8][9][10] have investigated about CO 2 flooding under the various miscibility conditions and the gravity drainage mechanism, none of researches have been done in vertical oil reservoir.…”
Section: Introductionmentioning
confidence: 99%